Improving Teaching Standards at Islamic Schools - Didin Syafruddin (Studia Islamika, 2005)
The main purpose of this research project is to examine the implementation of Islamic Primary Teacher Education (IPTE) programs in Islamic higher education institutions in Indonesia (i.e. UIN/IAIN/STAIN). More specifically this study seeks to look more closely at such issues as poLicy development of IPTE; Orientation of academic and institutional development of IPTE UIN, IAIN, and STAIN; academic standards, the student selection system for IPTE (including the number of student enrollments and admissions), the gender ratio (of both students and teachers), and the educational and socio-economic background of the students' parents; levels of satisfaction amongst teachers.DOI: 10.15408/sdi.v12i3.587